Cluster-based CaII, MgII and CdII coordination polymers based on amino-functionalized tri-phenyl tetra-carboxylate: Bi-functional photo-luminescent sensing for Fe3+ and antibiotics. (November 2019) - Li, Xin Shu; An, Jun Dan; Zhang, Hui Min; Liu, Jun Jie; Li, Yong; Du, Gui Xiang; Wu, Xiang Xia; Fei, Ling; Lacoste, Jed D.; Cai, Zheng; Liu, Yuan Yuan; Huo, Jian Zhong; et al.
Abstract: Excess and deficiency of iron(III) and antibiotics from normal permissible limits will induce serious disorders, so their detection is important but challenging. In this work, the asymmetric amino-functionalized tetra-carboxylate H4 L (2′-amino-1, 1':4′, 1″-terphenyl-3, 3″, 5, 5″-tetracarboxylic acid) containing large conjugated ter-phenyl aromatic backbones have been synthesized and employed. Through a one-pot powerful solvo-thermal synthetic strategy, a series of unique tri-nuclear cluster-based Ca II, Mg II and Cd II coordination polymers, namely [Ca1.5 ( μ 8 -HL)(DMF)]n (1 ), [Mg1.5 ( μ 7 -HL)·(H2 O)2 ]·3H2 On (2 ) and [Cd1.5 ( μ 10 -L)0.75 ]n ·H2 O·DMFn (3 ) have been successfully prepared.1 –3 exhibit excellent photo-luminescent properties and good fluorescence stability. Structural analyses reveal that tri-nuclear Ca II secondary building blocks (SBUS) are linked via HL 3−, forming the 2D clustered-based micro-porous coordination polymer1 . As for2, three carboxylate groups of partly de-pronated HL 3− also link these neighboring tri-nuclear Mg II SBUS, which constructs the 2D Mg II coordination framework2 . As for3, fully de-pronated L 4− also links these neighboring tri-nuclear Cd II SBUS, which ultimately constructs the 3D micro-porous coordination framework3. Experimental powder x-ray diffraction (PXRD) patterns coincide well with the theoretical patterns, which indicate that we have successfully synthesized the pure phase material1 –3 . Photo-luminescent experiments demonstrate that coordination polymers1 –3 can be successfully applied towards bi-functional sensing for sensitive detection of Fe 3+ and the antibiotics NZF (Nitrofurazone). To the best of our knowledge, this is the first example of the application of amino-functionalized tri-phenyl tetra-carboxylate based MOFs towards bi-functional discrimination of Fe 3+ and NZF antibiotics with high efficiency Ksv values (For Fe 3+ : 7.28 × 10 4 M −1 for1 ; 3.38 × 10 4 M −1 for2 and 3.29 × 10 4 M −1 for3 and for NZF antibiotics: 4.47 × 10 3 M −1 for1 ; 4 × 10 3 M −1 for2 and 5.6 × 10 3 M −1 for3 ). Graphical abstract: Image 1 Highlights: 1. The asymmetric amino-functionalized tetra-carboxylate H4 L containing conjugated ter-phenyl backbones have been employed. A series of unique tri-nuclear cluster-based Ca II, Mg II and Cd II coordination materials have been successfully prepared. This is the first example of tri-phenyl tetra-carboxylate based MOFs as bi-functional discrimination for Fe 3+ and NZF.